Characteristics of Unloading Creep of Tuffaceous Sandstone in East Tianshan Tunnel under Freeze-Thaw Cycles - Zhijun Zhou; Haochen Zhan; Jiangyang Hu; Chenning Ren (Advances in Materials Science and Engineering)
The physicomechanical properties of tunnel surrounding rock are influenced by many factors such as the external environment and freeze-thaw cycles, especially in engineering in high cold regions. To understand the characteristics of freeze-thaw cycles on the creep properties of rocks in high cold regions, a freeze-thaw test, SEM test, triaxial compression test, and triaxial unloading creep test were carried out for tuffaceous sandstone in the G575 East Tianshan Tunnel in Hami, Xinjiang. The results show the following: (1) the freeze-thaw cycle reduces the degree of cementation of mineral particles in a microcosm, manifested on a macro scale by the scaling mode and crack propagation mode; (2) the effect of freeze-thaw cycles reduces the compressive strength and shear strength of rock samples (i.e., ductility enhancement); (3) for tuffaceous sandstone, the unloading process and freeze-thaw cycle each lead to improved creep deformation in rock samples, and radial deformation is more sensitive to rock deformation and failure; and (4) the creep rate of surrounding rock can be reduced by confining pressure. The peak creep rate increased with freeze-thaw time, as did the overall creep rate. Attention should be paid to deformation within a short period, and necessary supporting and protection measures should be taken to reduce creep.